Is there any link between vitamin D and left atrial diameter in children? Vitamin D and Left Atrial Diameter - Cerit, Zeynep; Gökçe, Şule; Cerit, Levent (Progress in Nutrition, 2019)
Vitamin D (vitD) deficiency has been found associated with rickets/osteomalacia, autoimmune diseases, cardiovascular system diseases, and infectious diseases. Growing evidence demonstrated that vitD has a key role in the renin-angiotensin-aldosterone system. Although there is a strong association between left atrial diameter and serum vitD level in adults, there is scarce data in children. Therefore, we aimed to assess the association between serum vitD level and left atrial diameter in children. We performed a prospective study with 97 children in routine control without any complaint. All patients were evaluated for the echocardiographic evaluation in the outpatients clinic, and the children were divided into two groups as vitamin D deficiency group (vitamin D<20ng/ml) and control group (vitamin D≥20ng/ml). Demographic data, echocardiographic parameters, and serum vitD level were analysed. A p-value of <0.05 was considered significant. The study population included 97 children, and the prevalence of vitD deficiency was found 46.3%. Although left atrial diameter was increased in children with vitD deficiency, there was no significant difference between the two groups with regard to left atrial diameters. Left atrial diameter was significantly associated with BMI z-score (r=0.301), age (r=0.307)(P<0.001), interventricular septum (r=0.209), weight (r=0.184), vitD (r=0.127). On multivariate analysis, BMI z-score was significantly associated with left atrial diameter. BMI z-score is independently associated with left atrial diameter. Although left atrial diameter was increased in patients with vitD deficiency, serum vitamin D level was not found an independently associated with the left atrial diameter.